Pharmacological targeting of G protein-coupled receptor heteromers. (November 2022) - Moreno, Estefanía; Casajuana-Martin, Nil; Coyle, Michael; Campos, Baruc Campos; Galaj, Ewa; del Torrent, Claudia Llinas; Seyedian, Arta; Rea, William; Cai, Ning-Sheng; Bonifazi, Alessandro; Florán, Benjamín; Xi, Zheng-Xiong; et al.
Abstract: A main rationale for the role of G protein-coupled receptor (GPCR) heteromers as targets for drug development is the putative ability of selective ligands for specific GPCRs to change their pharmacological properties upon GPCR heteromerization. The present study provides a proof of concept for this rationale by demonstrating that heteromerization of dopamine D1 and D3 receptors (D1 R and D3 R) influences the pharmacological properties of three structurally similar selective dopamine D3 R ligands, the phenylpiperazine derivatives PG01042, PG01037 and VK4–116. By using D1 R-D3 R heteromer-disrupting peptides, it could be demonstrated that the three D3 R ligands display different D1 R-D3 R heteromer-dependent pharmacological properties: PG01042, acting as G protein-biased agonist, counteracted D1 R-mediated signaling in the D1 R-D3 R heteromer; PG01037, acting as a D3 R antagonist cross-antagonized D1 R-mediated signaling in the D1 R-D3 R heteromer; and VK4–116 specifically acted as a ß-arrestin-biased agonist in the D1 R-D3 R heteromer. Molecular dynamics simulations predicted potential molecular mechanisms mediating these qualitatively different pharmacological properties of the selective D3 R ligands that are dependent on D1 R-D3 R heteromerization. The results of in vitro experiments were paralleled by qualitatively different pharmacological properties of the D3 R ligands in vivo . The results supported the involvement of D1 R-D3 R heteromers in the locomotor activation by D1 R agonists in reserpinized mice and L -DOPA-induced dyskinesia in rats, highlighting the D1 R-D3 R heteromer as a main pharmacological target for L -DOPA-induced dyskinesia in Parkinson's disease. More generally, the present study implies that when suspecting its pathogenetic role, a GPCR heteromer, and not its individual GPCR units, should be considered as main target for drug development. Graphical Abstract: ga1